Manejo da irrigação com combinações de adubos químicos e orgânicos na cultura do rabanete no litoral nordestino - Silva, Luana Soares da (2017)
The objective of this study was to evaluate the relationship between irrigation sludge and fertilizer types in two experiments to define an optimized irrigation management and to verify the viability and use of organic residues in radish production. The experiments were conducted in the experimental area of the Agrometeorological Station of the Universidade Federal do Ceará, Fortaleza, Brazil. The experimental design was a randomized block design, in 5 x 5 subdivided plots, with four replications and three plants per pot. In the first field experiment, the primary treatments were five irrigation slides (30%, 60%, 90%, 120%, and 150% of the reference evapotranspiration estimated by the Class “A” tank method), and the secondary treatments were one (fertilizer, biofertilizer, mineral fertilizer + biofertilizer, and biofertilizer + vegetable ash). In the second experiment, in the protected environment, the primary treatments were five irrigation slides (30%, 60%, 90%, 120% and 150% of the reference evapotranspiration estimated by the Class A tank method), and the secondary treatments were a witness and four types of fertilizers (control, mineral fertilizer, mineral fertilizer + vegetable ash, vegetable ash, and biofertilizer + vegetable ash). The following responses were analyzed: fresh tuber mass; dry mass of tuber; tuber length; tuber diameter; fresh shoot mass; dry shoot mass; leaf area; and productivity. In the first experiment, all the response variables were significantly influenced only by the fertilizer factor. In the second experiment, except for the tuber diameter, which was influenced by the interaction between the irrigation blade and the fertilizer, the other response variables were also significantly influenced only by the fertilizer factor. In the first experiment, the best fertilizer for most response variables is the combination of biofertilizer + mineral fertilizer. In the second experiment, the best fertilizers for most variables are the combination of biofertilizer + mineral fertilizer and mineral fertilizer.